Determinan Terpenting Dari Pengelolaan Keuangan Bagi Pegawai Yang Bekerja Pada Organisasi Publik - Tanjung, Hasrudy; Putri, Linzzy Pratami; Adha, Fhaira Tania Nur (Magister Akuntansi Universitas Pancasila, 2023)
Seeing how the concept of financial literacy has dominated as a potential predictor of quality financial management, this study aims to examine the effect of self-control, financial attitudes on financial management directly or indirectly through financial literacy. The unit of analysis specified in this study is employees working in the public sector, with the research object being employees working at BKKBN in North Sumatra Province. A total of 91 employees who were respondents in this study participated in answering a complete research survey that was distributed online. The data that has been collected is analyzed using path analysis. The research findings indicate that there is one path that is found to be insignificant, namely the effect of self-control on financial management. Compared to financial attitudes, self-control was found to be the most important determinant of financial literacy. Meanwhile, financial attitude was found to be the most important determining factor of the financial management of North Sumatra Province BKKBN employees.